A Simple Method to Extract Mitochondrial DNA in a Non-invasive Phylogenetic Study of Domestic Native Thai Ducks - Piyanan Leekaew; Thaweesak Songserm; Apassara Choothesa; Ukadej Boonyaprakob (Agriculture and Natural Resources, 2008)
A simple low-cost method for extracting mitochondrial DNA (mtDNA) from a single plucked feather for a non-invasive genetic study of ducks is described. The mtDNA was isolated via alkaline lysis, and after neutralization, the crude DNA-containing lysate was used directly for PCR. We have had a 100% (30/30) success in amplification of a 710-bp fragment of the mtDNA control D-loop region. Sequence analysis and phylogenetic relationship of the 667-bp D-loop segments of the two domestic native Thai ducks, Nakorn-Pathom (NP) and Park-Nam (PN), was further investigated. Two breeds exhibited 100% identity over the entire 667-bp products, although several types of mtDNA polymorphism were detected. Comparing the 667-bp D-loop sequence data with those of Anas ducks and Muscovy duck used as an outgroup showed that both native Thai ducks and Mallard (Anas platyrhynchos) haplotype A clustered together (bootstrap support 91%), indicating that there was common ancestor for those breeds. Here we report a quick, simple, reliable and inexpensive DNA extraction procedure for a duck’s feather. Our findings clearly demonstrate that the domestic native Thai ducks derive their origin from the Mallard group A haplotypes.